2015
DOI: 10.1038/nn.4143
|View full text |Cite
|
Sign up to set email alerts
|

Basal forebrain circuit for sleep-wake control

Abstract: The mammalian basal forebrain (BF) has important roles in controlling sleep and wakefulness, but the underlying neural circuit remains poorly understood. We examined the BF circuit by recording and optogenetically perturbing the activity of four genetically defined cell types across sleep-wake cycles and by comprehensively mapping their synaptic connections. Recordings from channelrhodopsin-2 (ChR2)-tagged neurons revealed that three BF cell types, cholinergic, glutamatergic and parvalbumin-positive (PV+) GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
537
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 441 publications
(579 citation statements)
references
References 57 publications
36
537
4
2
Order By: Relevance
“…Local BF afferents may also contain GABA and/or glutamate. Local inputs to cholinergic outputs both drive and inhibit ChAT cells, depending on afferent cell identity (Xu et al, 2015). Recent awake behaving physiological data indicate heterogeneous response patterns among BF units becoming activated and inhibited to different phases of a directed attention task (Tingley et al, 2014), patterns which may be carried by local subgroups of BF input impinging on different cholinergic output targets.…”
Section: Resultsmentioning
confidence: 99%
“…Local BF afferents may also contain GABA and/or glutamate. Local inputs to cholinergic outputs both drive and inhibit ChAT cells, depending on afferent cell identity (Xu et al, 2015). Recent awake behaving physiological data indicate heterogeneous response patterns among BF units becoming activated and inhibited to different phases of a directed attention task (Tingley et al, 2014), patterns which may be carried by local subgroups of BF input impinging on different cholinergic output targets.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that both these BF populations exhibit maximum firing rates above 50 Hz and thus could participate in rhythmic firing at the gamma frequencies reported in the present study. Interestingly, the glutamatergic projection has been shown to be inhibited by cholinergic activation (60,61), which would provide a mechanism by which the DMN is suppressed during externally directed attentional processing. However, the glutamatergic BF population does not support a pronounced projection to the DMN or even to cortex more generally.…”
Section: Discussionmentioning
confidence: 99%
“…These cholinergic neurons are known to project widely and diffusely, innervating neurons throughout the CNS. They also exhibit extensive local collaterals terminating on GABAergic neurons within the BF, thus controlling sleep and wakefulness [42,43]. We identified the fundamental role of the septo-hippocampal cholinergic system in the development of the behavioral deficits in Chat-Mecp2 −/y mice.…”
Section: Chat-mecp2mentioning
confidence: 97%